Sejarah Islam dan Politik di Afghanistan - Muhammad Farih Fanani; Adetia Andri (Fakultas Adab dan Humaniora UIN Raden Fatah, 2021)
Afghanistan is a country in Asia that has a long history. In the late 20th and early 21st centuries, Afghanistan experienced dark times. Their government was intervened by a foreign country. Moreover, Afghanistan was once controlled by the extremist group, namely the Taliban. The Taliban control Afghanistan and control most of Afghanistan, making Afghanistan a conflict-prone country. Even Afghanistan is ranked in the bottom two as a country that is prone to conflict. It was caused by various things. However, efforts to modernize Afghanistan have not stopped. The modernization process goes hand in hand with democratization. Even though there are still shortcomings in various sectors such as Human Rights, gender equality, press freedom, etc., Afghanistan is on the right path. This article discusses the history of Islam and politics in Afghanistan, including the journey in establishing a state, modernization efforts, and hopes for democratization in Afghanistan. This article uses a historical method and a political approach, so that it will be able to see historical and political events in Afghanistan from a political point of view. Keywords: Afghanistan, history, democratization. politic, Islam.